2014
DOI: 10.1002/chem.201406073
|View full text |Cite
|
Sign up to set email alerts
|

Macrocycle Embrace: Encapsulation of Fluoroarenes by m‐Phenylene Ethynylene Host

Abstract: We report structural characterization of a new member of m-phenylene ethynylene ring family. This shape-persistent macrocycle also co-crystallizes with hexafluoro-, 1,2,4,5-tetrafluoro-, 1,3,5-trifluoro, and 1,4-difluorobenzene. The four complexes are almost isostructural, and all show the fluoroarene included into the central cavity of the macrocycle. Characterized by multiple short C - H⋅⋅⋅F - C contacts, these inclusion complexes further dimerize in the solid state into a 2+2 assembly, in which the two macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 84 publications
(17 reference statements)
0
22
0
Order By: Relevance
“…However, for the IVM molecule, the electrostatic potential obtained from the DFT calculation of the distribution of electron density does not contain significant extrema. This is also the case for other macrocyclic molecules [40]. For this reason, molecules of IVM can form inclusion compounds with polar molecules due to the formation of hydrogen bonds.…”
Section: Molecular Structure In the Crystal Cellmentioning
confidence: 79%
“…However, for the IVM molecule, the electrostatic potential obtained from the DFT calculation of the distribution of electron density does not contain significant extrema. This is also the case for other macrocyclic molecules [40]. For this reason, molecules of IVM can form inclusion compounds with polar molecules due to the formation of hydrogen bonds.…”
Section: Molecular Structure In the Crystal Cellmentioning
confidence: 79%
“…Similar [π⋅⋅⋅π] stacking, wherein two molecules of 1 form a unique complex building block, is also observed in the structure of Zr‐MCMOF; this stacking distorts the Zr 6 secondary building unit (SBU) in Zr‐MCMOF, generating a layered structure rare among Zr‐based MOFs . In our previous work, an ester derivative of macrocycle 1 was shown to encapsulate fluoroarenes inside its cavity; thus, the 1D channels in Zr‐MCMOF appear to be a unique microenvironment, promising for applications in highly specific separations.…”
Section: Figurementioning
confidence: 99%
“…[6] Among the numerousS PMs, arylene ethynylenem acrocycles( AEMs) are the most widely studied and many interesting applications based on AEMs have emerged. [7][8][9][10][11][12][13][14] Recent advances in dynamic covalent chemistry, [15][16][17] namely alkyne metathesis, have enabled the facile access to AEMs on gram scale, and boosted the applicationso ft hese macrocycles towardm aterials development. [18][19][20] It has been reported that the self-association of AEMs is induced by face-to-face p-p interactions between aromatic rings and is strongly influenced by the rigidity of the backbone structuresa nd pendant functional groups of the macrocycles: Electron-withdrawings ubstituents promotes elf-aggregation of macrocycles, whereas electron-donating functional groups have the opposite effect;ap lanar and rigid framework enhances the aggregation, whereas aflexible nonplanar geometry inhibits it.…”
Section: Introductionmentioning
confidence: 99%